Features of seborrheic keratoses in patients with carbohydrate metabolism disorders - A. K. Alexandrova; V. A. Smolyannikova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Multiple seborrheic keratosis (SK), especially when there is overexpression of the epidermal growth factor receptor (EGFR), is considered paraneoplastic dermatosis, but it is almost always associated with multiple fibroepithelial polyps (PF) and pseudoacanthosis, skin diseases in which the leading role is played by insulin resistance and type 2 diabetes mellitus. The study examines the possibility of the effect of disorders of carbohydrate metabolism on the clinical picture of multiple SK and the expression of EGFR.Aims. To study the clinical features of multiple SC and the expression of EGFR in patients, depending on the presence of concomitant type 2 diabetes mellitus.Materials and methods. There were 65 patients with multiple SK at the age from 55 to 77 years, including women (44) and men (21). All the patients were examined skin, consultation of the endocrinologist. For a histological and immunohis-tochemical study (IHC), a single SK was surgically excised in each patient. IHC-reactions were carried out with monoclonal antibodies to EGFR. The result was assessed by the number of stained cytoplasmic membranes of tumor cells.Results. In 81.5 % of cases, multiple SK was associated in patients with type 2 diabetes mellitus. The location of the SK was also characteristic mainly in large folds of the skin, in contrast to patients without disorders of carbohydrate metabolism, in which the SK were located mainly on the lateral surfaces of the trunk and abdomen, without affecting the large folds of the skin. Multiple PF were also characteristic of individuals with type 2 diabetes mellitus. In IHC studies EGFR expression was detected in 100 % of cases in individuals with multiple SC and type 2 diabetes mellitus in over 30 % of tumor cells, and only in 16.7 % of cases in individuals with multiple SK without violations of carbohydrate metabolism.Conclusions. The presence of multiple SK in patients, in combination with multiple PFs with characteristic tumor localization in large folds of the skin, serves as a diagnostic marker of carbohydrate metabolism disorders or predispositions to the development of type 2 diabetes. Increased expression of EGFR plays a leading role in the pathogenesis of multiple SK, stimulating the proliferation and growth of SK, in turn, as a consequence of impairment of insulin signaling pathways and insulin resistance.